1999
DOI: 10.1002/hep.510300515
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity to endotoxemia in the bile duct-ligated cirrhotic rat

Abstract: Sepsis is a common complication of cirrhosis with a high mortality. In this study, we have investigated some of the pathways that may be involved in tissue injury and death. Bile duct-ligated (BDL) cirrhotic and control rats were challenged with lipopolysaccharide (LPS). Sensitivity to LPS was markedly enhanced in the BDL group, and was associated with increased liver injury and mortality. There was a 5-fold constitutive activation of nuclear factor B (NFB) in the liver of BDL rat controls (P F .001), and this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
98
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 49 publications
6
98
1
Order By: Relevance
“…These data confirm and extend previous studies in bdl ro- dents. 9,[11][12][13][14] In earlier studies in rodents, 9,10 we showed that endotoxin sensitivity is increased after bdl, and rises further when endotoxin transport to the cholestatic liver is increased by binding with (reconstituted) high density lipoprotein. 9 Humans with biliary obstruction also show evidence for enhanced susceptibility to endotoxin.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…These data confirm and extend previous studies in bdl ro- dents. 9,[11][12][13][14] In earlier studies in rodents, 9,10 we showed that endotoxin sensitivity is increased after bdl, and rises further when endotoxin transport to the cholestatic liver is increased by binding with (reconstituted) high density lipoprotein. 9 Humans with biliary obstruction also show evidence for enhanced susceptibility to endotoxin.…”
Section: Discussionmentioning
confidence: 79%
“…9 In addition, cholestasis is associated with enhanced susceptibility toward endotoxin-induced toxicity. [9][10][11][12][13][14] Endotoxin exerts its biological effects by activating immunocompetent cells such as monocytes and macrophages. After exposure to endotoxin, these cells readily release various inflammatory mediators such as the cytokines tumor necrosis factor (TNF) and interleukin-1 (IL-1), 15 which leads to an inflammatory response.…”
mentioning
confidence: 99%
“…In contrast, previous papers reported that BDL mice produced a large amount of TNF-␣ after LPS stimulation. 11,32 This may reflect a difference of LPS versus whole bacterial challenge. In fact, we found in our experimental model that serum TNF-␣ levels of BDL mice were more than 10 times higher than those of sham-operated mice 1 hour after 4 mg/kg LPS injection (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 It is also demonstrated that rats and mice with experimental obstructive jaundice produce higher levels of proinflammatory cytokines including TNF-␣, IL-1, and IL-6 after lipopolysaccharide (LPS) injection compared with those without obstructive jaundice, and that cholestatic animals are susceptible to LPS-induced organ failure and mortality. [11][12][13] However, involvement of anti-inflammatory cytokines in host resistance to bacterial infection in cholestasis or cy-tokine profile in response to exogenously administered viable bacteria in cholestatic animals remains to be elucidated.…”
mentioning
confidence: 99%
“…Liver specimens were collected at 5 h after LPS injection, at the end of the experiments. The LPS treatment concentration was set at 5 ㎎/㎏ based on the finding that this concentration has been shown to cause endotoxin shock in rats and mice over a short period of time, raising the cytokine concentrations in the liver and blood (Corral et al, 1996;Aono et al, 1997;Harry et al, 1999;Sang et al, 1999).…”
Section: Animal Experimentsmentioning
confidence: 99%